2012
DOI: 10.1186/1750-1172-7-77
|View full text |Cite
|
Sign up to set email alerts
|

The French Gaucher’s disease registry: clinical characteristics, complications and treatment of 562 patients

Abstract: BackgroundClinical features, complications and treatments of Gaucher’s disease (GD), a rare autosomal–recessive disorder due to a confirmed lysosomal enzyme (glucocerebrosidase) deficiency, are described.MethodsAll patients with known GD, living in France, with ≥1 consultations (1980–2010), were included in the French GD registry, yielding the following 4 groups: the entire cohort, with clinical description; and its subgroups: patients with ≥1 follow-up visits, to investigate complications; recently followed (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 44 publications
(37 reference statements)
7
88
2
5
Order By: Relevance
“…Our results confirmed that a BE before ERT increases the risk of a BE during ERT (24). For the next step, we should analyze the complete follow-up of patients, taking into account the initiation of ERT as a time-dependent covariate to test the impact of ERT on the change in BEs occurrence.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Our results confirmed that a BE before ERT increases the risk of a BE during ERT (24). For the next step, we should analyze the complete follow-up of patients, taking into account the initiation of ERT as a time-dependent covariate to test the impact of ERT on the change in BEs occurrence.…”
Section: Discussionsupporting
confidence: 78%
“…We used frailty model to analyze data from the FGDR (24). More precisely, we studied the occurrence of repeated BEs in Gaucher patients, since the initiation of treatment (time=0) by imiglucerase monotherapy.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zu den skelettalen Manifestationen zählen die Infiltration des Knochenmarks mit Gaucher-Zellen, eine Verminderung der Knochendichte, avaskuläre Nekrosen, Knochenschmerzen, Gelenkzerstörungen und Spontanfrakturen. Irreversible Knochenschäden können orthopädische Eingriffe und einen Gelenkersatz nötig machen sowie zu Behinderungen führen [1,[4][5][6][7][8][9][10]. Unbehandelt reduziert die Gauchererkrankung Typ 1 die Lebenserwartung erheblich [11]; im Langzeitverlauf können zusätzlich zu den o. g. Komplikationen eine Lungenfibrose mit pulmonaler Hypertonie und eine Leberzirrhose mit portaler Hypertension sowie gehäuft multiple Myelome und B-Zelllymphome und sogar schwere Augenkomplikationen auftreten [1,2,4,8,12,13].…”
Section: Stellungnahme Der Deutschen Gesellschaft Für Gastroenterologunclassified